Recommendations for designing collaborative activities in online higher education: a systematic review - Elisabeth Ransanz Reyes; Ainhoa Arana-Cuenca; Ana Isabel Manzanal Martínez (Journal of Technology and Science Education)
Online learning, especially in higher education, has grown in recent years and the study of its didactic implications has also increased. Online experiences have been found to be as successful as face-to-face ones, but there is a concern about a lack of social interaction among students. This makes it necessary for teachers to plan collaborative activities. Therefore, the aim of the present work is to analyse the main design features of collaborative activities that have been reported as successful in higher education. A total of 46 articles published between the years 2018 and 2023 were analysed in a systematic review based on the PRISMA Statement. Their main elements were grouped into three categories: contextual factors; pedagogical strategies; and ICT tools and resources that favour the development of such activities. By way of conclusion, recommendations for the design and instruction of a collaborative higher education activity in an online environment are presented.